2014
DOI: 10.4081/jlimnol.2014.820
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton dynamic and bioindication in the Kondopoga Bay, Lake Onego (Northern Russia)

Abstract: On the basis of our collected material and historical information we assess phytoplankton dynamics in Kondopoga Bay, the Lake Onego in [1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008][2009][2010][2011]. The summer communities from continuously studied sampling stations contain 100 species belonging to eight divisions: Bacillariophyta, 40; Chlorophyta, 25; Cyanobacteria, 13; Chrysophyta, 12; Euglenophyta, 2; Dinophyta, 4; Cryptophyta, 3; and Xanthophyta, 1. Sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…We have previously shown that, between Shannon Bi and the average mass of the algal cell, the correlation can be both negative (Barinova and Chekryzheva, 2014;Krupa et al, 2016), and positive (Krupa and Barinova, 2017). Analysis of large data sets showed that a positive relationship between diversity and organism body size is reflected in the relatively early stage of succession of plankton communities (Krupa and Barinova, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that, between Shannon Bi and the average mass of the algal cell, the correlation can be both negative (Barinova and Chekryzheva, 2014;Krupa et al, 2016), and positive (Krupa and Barinova, 2017). Analysis of large data sets showed that a positive relationship between diversity and organism body size is reflected in the relatively early stage of succession of plankton communities (Krupa and Barinova, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…in 40 km north of Almaty. Its maximum depth is 20 m, the water surface is about 58 km 2 . The potential volume of the reservoir, taking into account the height of the dam is about 1,000 million m 3 at the altitude of its surface of about 622 m. Sorbulak is one of the largest wastewater storage facilities.…”
Section: Introductionmentioning
confidence: 99%
“…During this investigation, Bacillariophyceae flora is the dominant taxa in Sidi Abderrahmane waters with 25 species. Barinova and Chekryzheva (2014) concluded that the dominance of Bacillariophyceae in a temperate lake is an indicator of its oligotrophic status. The algal population was mainly dominated by the Cyanophyceae Oscillatoria sp .…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan kehadiran jenis fitoplankton pada penelitian ini, terdapat perubahan jenis penyusun komposisi di setiap periode. Hal tersebut diduga telah terjadi perubahan kualitas ataupun nutrien di perairan (Barinova & Chekryzheva, 2014;Jindal et al, 2014).…”
Section: Komposisi Sebaran Fitoplankton Dan Zooplanktonunclassified